The Representation of Queer Identities in The Seven Husbands of Evelyn Hugo (2017) by Taylor Jenkins Reid - Inkeröinen, Riina (My University, 2022)
My thesis focuses on how queer identities are represented in Taylor Jenkins Reid’s novel The Seven Husbands of Evelyn Hugo (2017). My aim is to analyze how the queer identities of the three main characters develop as they live and work in Hollywood, where their sexualities are not accepted by the surrounding society. I use queer theory as the framework of my analysis and tie the significant terms and questions of the literary field to my research through examples from the primary text. I refer to the works of Eve Kosofsky Sedgwick, Adrienne Rich, and Judith Butler. The novel’s protagonist, Evelyn Hugo, is an ambitious actress in Hollywood from the 1950s onwards, who must hide her bisexuality from the public. I also analyze the lesbian character Celia St. James and the gay character Harry Cameron. The characters are forced to separate their public and private lives from each other to keep working in the movie industry. The queer identities of the characters are influenced by their self-image, as well as the relationships that they have. There are oppressive structures set in place in the society and in Hollywood, where people belonging to any sexual minority struggle with being prejudiced against because of their sexuality. White and heterosexual actors and actresses are seen as the more marketable option and the characters try to present themselves as such. Actively hiding one’s sexuality leads to the characters battling with their own true identities.
Keywords: Queer theory, Identity, Self-image, Bisexuality, LGBTQIA+, Gay Liberation, Lesbian Feminism, Compulsory Heterosexuality, Queer Literature, North American Literature, Historical Fiction, Taylor Jenkins Reid, The Seven Husbands of Evelyn Hugo